Dual educational rationality and acculturation in Mapuche people in Chile - Quilaqueo, Daniel; Riquelme, Enrique; Paez, Darío; Mera-Lemp, María José (Frontiers in Psychology, 2023)
This article addresses the “logic of double rationality” in the educational knowledge of the Mapuche people, in Chile, and its link with acculturation dynamics from Berry's model. The frame of reference supports an epistemic base of Mapuche educational knowledge and the notion of relationship with knowledge, as well as the dynamics of acculturation proposed by Berry. The aim is to explore the double Mapuche/ “Mestizo” educational rationality in relation to acculturation processes. A total of 468 Mapuche people between the ages of 17 and 53 (M=16.19; SD=7.0), high school and college students from urban and rural areas of different regions of Chile, participated in the study. Biculturalism or integration characterized 39.4%, segregation or ethnic identity 23.5%, assimilation 17.5% and marginalization 20.7%. The results indicate that people identified as bicultural scored higher in the components of dual Mapuche/ Chilean Mestizo educational rationality, and positive and negative associations were observed between the bicultural acculturation and assimilation profiles and the educational level of the participants, respectively. The higher the fluency in speaking Mapunzugun or Mapuche language, the higher the perception of cultural difference in knowledge and education between Mapuche and Chilean culture, the positive evaluation of the teaching of Mapuche culture, the perception of school as a factor of assimilation, the valuation of bicultural practices and the justification of double rationality. The article concludes by projecting the findings in the school context for a pertinent education in contexts of social and cultural diversity.